Answer: 5x + y = 13 / y = -5x + 13
Explanation:
If you want to know if these points are in a equation, you have to check each point in each equation.
So.. let's try. We have the first point (2,3). Now, we're checking in the first equation:
5 . (2) + (3) = 13 (this is a true sentence)
Let's try the another point (4, -7)
5.(4) + (-7) = 13 (this is a true sentence as well)
the second one: y + 7 = -5(x + 4)
3 + 7 = -5(2+6) (it isn't true. So, I won't try the another point).
the third one: y = -5x + 13
(3) = -5.(2) + 13 (this is a true sentence. Let's check now the another point).
(-7) = -5(4) + 13 (this is a true sentence as well).
the fourth one: y - 7 = 5(x + 4)
(3) - 7 = 5(2 + 4) (it isn't true. I won't check the another point).
Finally, we have as a answer the first and the third equations.